Odpowiedzi

2009-11-23T19:25:55+01:00
2x-y=10
x+5y=-17

2x-y=10
x=-5y-17

2*(-5y-17)-y=10
x=-5y-17

-10y-34=10
x=-5y-17

-10y=34+10
x=-5y-17

-10y=44 /-10
x=-5y-17

y=-4,4
x=-5*(-4,4)-17

y=-4,4
x=-22-17

y=-4,4
x=-39



2009-11-23T19:36:04+01:00
A)
2x-y=10/*5
x+5y=-17

10x-5y=50
x+5y=-17

x+10x+5y-5y=50-17
11x=33
x=3
3+5y=-17
5y=-20
y=-4
x=3

b)
3m+n=9/*5
2m-5n=-11

15m+5n=45
2m-5n=-11

15m+2m+5n-5n=45-11
17m=34
m=2
3*2+n=9
6+n=9
n=3
m=2

c)
4a-2=b/*7
3a+7b=1,5

28a-14=7b
3a+28a-14=1,5

31a=15,5
a=0,5
0,5*4-2=b
b=0
a=0,5

d)
5x=4-2y
4x+y=3/*2

8x+2y=6
4-2y=5x

8x+2y+4-2y=5x
8x+4=5x
5x-8x=4
-3x=4
x=-4/3
4-2y=5*-4/3
-2y=-20/3 -4
2y=20/3 +4
y=10/3 +2
y=16/3
x=-4/3

e)
6x-3y=9
x+5y=-9,5 /*-6

-6x-30y=57
6x-3y=9
6x-6x-30y-3y=9+57
-33y=66
y=-2
x+2*-2=-9,5
x-4=-9,5
x=-5,5
y=-2
2009-11-23T19:37:31+01:00

a) 2x-y=10
x+5y=-17

y=-10+2x
x+5(-10+2x)=-17

y=-10+2x
x-50+10x=-17

y=-10+2x
11x=-17+50

y=-10+2x
x=3

y=-10+6
y=-4

b) 3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m)=-11
2m-45+15m=-11
17m=34
m=2

n=9-3*2
n=3

c) 4a-2=b
3a+7b=1,5

3a+7(4a-2)=1,5
3a+28a-14=1,5
31a=15,5
a=0,5

b=4*0,5-2
b=0

d) 5x=4-2y
4x+y=3

y=3-4x

5x=4-6+8x
-3x=-2
x=2/3

y=3-4*2/3
y=1/3

e) 6x-3y=9
x+5y=-9,5

x=-9,5-5y

6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2

x=-9,5-5*-2
x=0,5